Empoderamiento de la Mujer Rural de Asoagrotoca y su Producción de papa. (2020)
Women in the rural sector have had to live in society and at home in social, economic and cultural inequalities, adapting to machismo that throughout their lives they have lived being traditional for them, without recognition of their rights, where they have had to living situations of extreme poverty, since a difference of men have had less possibilities of access to education, land ownership, formal and / or decent employment, opportunities to obtain stable and well-paid jobs, because they keep in mind that in agricultural work it is one more household activity. Therefore, the purpose of the project is to show the empowerment of rural women in the Asoagrotoca Association of the municipality of Toca Boyacá; It is to be considered that they have had to face many obstacles in order to achieve optimal participation in agriculture, but through association they have achieved social, economic growth and their quality of life, being now a fundamental part of the Association and the home. for decision making. The barriers to gender inequality that will be seen little by little will gradually disappear, since these peasant women will have greater recognition by society, motivating them to continue improving personally and to be more productive in the work of the fields. What you want to achieve within the Association is that there are developed women, abilities and skills that contribute to total empowerment, for this reason an improvement plan was designed, where you can obtain the interview and a survey that served as a guide. diagnosis to show that they have shortcomings in order to develop an action plan that will enrich their knowledge.